American Studies and the Canonization of Thomas Pynchon - Grgas-Mufa, Stipe (Array, 2013)
Reviewing the extant paradigms of American Studies the author points out the erasure of capital from their readings. Arguing for the retrieval of capital in the disciplinary research agenda and maintaing that literature still provides an archive for reading the US polity he atgues for the canonical status of Thomas Pynchon as the writer who has throughout his opus engaged the issue of American capitalism.